ANALYSIS OF WAYS TO IMPROVE CONSTITUTIONAL REGULATION IN THE RUSSIAN FEDERATION - Nurmagambetov , Rashit (Revista Inclusiones, 2020)
The factor that has led to the analysis of various problems of constitutional regulation is the lack of systematic scientific knowledge about the existing theoretical and legal problems of the phenomenon in focus and the ways of its improvement. This has posed a task of specifying the existing technical, legal, logical, grammatical inconsistencies, gaps and defects of the Constitution of the Russian Federation and working out effective ways to overcome them. Among such problems is the presence in the text of the Russian Constitution of a large number of hidden terms that implying a different content, the non-observance of the logical sequence of the use of terms, the inaccurate use of verbal moods. The purpose of the present article is to analyze the ways to improve the constitutional regulation of the Russian Federation as a political and legal phenomenon. The leading method of research is the comparative legal method that makes it possible to identify the urgent theoretical and legal problems of constitutional regulation. The result of the study consists in the description of effective ways to overcome problems of constitutional regulation in the Russian Federation. In particular, it is proposed to organize on a continuing basis activities aimed at including in the legal dictionaries and doctrinal comments the terminology that reveals the content of constitutional regulation, and to work on the diversification of its methodology. The materials of the article can be useful for the representatives of the legal science of the countries of the Romano-Germanic legal family, scholars in the field of constitutional comparative law, and students of law schools.